Two for the money - Caruso, D. J.; Cohen, Jay.; Robinson, David C.; Robinson, James G.; Gilroy, Dan, 1959-; Pacino, Al, 1940-; McConaughey, Matthew, 1969-; Russo, Rene.; Assante, Armand, 1949-; Piven, Jeremy; King, Jaime, 1979-; Hall, Conrad W.; et al. (Universal City, CA : Universal Pictures, 2006)
Brandon's talent makes him a prime candidate for recruitment by Walter Abrams, the head of one of the biggest sports consulting operations in the country. Walter hires the small town ex-athlete and grooms him into a shrewd front man. Brandon soon begins to enjoy his status as a Manhattan golden boy and finds himself growing comfortable with Walter's high-rolling lifestyle. The surrogate father/surrogate son relationship fattens Walter's business and personal accounts. That is until Brandon's golden touch begins to falter at the same time that Walter's manipulation of his protege crosses the line.
DVD release of the 2005 motion picture.
Special features: feature commentary with D.J. Caruso and Dan Gilroy ; "The making of 'Two for the money'" ; insider interview: "The real Brandon" ; deleted scenes (with optional commentaries) ; theatrical trailer and TV spots ; Universal trailers.
Al Pacino, Matthew McConaughey, Rene Russo, Armand Assante, Jeremy Piven, Jaime King, Kevin Chapman, Ralph Garmen, Gedde Watanabe.
DVD ; region 1 ; full screen (1.33:1) presentation ; Dolby Digital 5.1 surround, dual layer, single sided.
Keywords: Consultants -- New York (State) -- New York; Manipulative behavior -- New York (State) -- New York; Employees -- Recruiting -- New York (State) -- New York; Consultants; Feature films; Video recordings for the hearing impaired; Sport; Thriller